(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid advancements in Artificial Intelligence (AI) have reshaped the way individuals engage with information, particularly in the educational context worldwide. AI technologies, which have evolved significantly in recent years (Moon et al., 2024) are transforming how students acquire, process, and evaluate information. Today’s generation of learners is increasingly interacting with AI tools, often without realizing their impact on learning outcomes. This global trend calls for a reevaluation of educational strategies to align with the digital competencies and critical thinking skills required in the modern world. As AI becomes deeply integrated into classrooms worldwide, it is vital to understand its influence on students’ ability to seek, assess, and utilize information, particularly in subjects like Social Studies, which demand analytical and evaluative skills. This research investigates the influence of AI tools on the information literacy skills of Grade 10 students, with a focus on Social Studies. The study centers on Pantay Integrated High School in Tanauan City, Batangas, Philippines, chosen for its unique characteristics. This school offers Social Studies as a core subject and incorporates a curriculum that addresses contemporary issues, making it an ideal context for exploring the impact of AI on information literacy. Furthermore, the students’ access to various AI tools provides a relevant setting to analyze how these technologies support or challenge their ability to evaluate, retrieve, and synthesize information. AI has shown immense potential to enhance educational efficiency, such as automating repetitive tasks and providing personalized learning experiences (Wen, 2024). These benefits improve how students interact with academic content. However, concerns persist regarding over-reliance on AI tools, (Hua, 2023) which could diminish students’ ability to critically assess the credibility of sources and foster ethical awareness (Murray, 2023). The importance of AI in improving students’ information literacy is evident in its ability to assist in key areas such as information retrieval, evaluation, and synthesis. Studies indicate that AI-powered tools enhance students’ ability to critically assess sources and engage with diverse perspectives (D'Angelo et al., 2022). For example, AI can provide personalized learning experiences, facilitating targeted instruction based on individual progress and preferences (Bennani et al., 2021). In Social Studies, these capabilities enable students to gain deeper insights into complex topics and analyze issues effectively. However, (Ng, 2023) questions remain regarding how these tools shape students' cognitive and ethical engagement with information (Sebetci, 2019).